Reduced graphene oxide-loaded nanocomposite scaffolds for enhancing angiogenesis in tissue engineering applications. Issue 5 (2nd May 2018) - Chakraborty, S.; Ponrasu, T.; Chandel, S.; Dixit, M.; Muthuvijayan, V.
Abstract : Tissue engineering combines cells, scaffolds and signalling molecules to synthesize tissues in vitro . However, the lack of a functioning vascular network severely limits the effective size of a tissue-engineered construct. In this work, we have assessed the potential of reduced graphene oxide (rGO), a non-protein pro-angiogenic moiety, for enhancing angiogenesis in tissue engineering applications. Polyvinyl alcohol/carboxymethyl cellulose (PVA/CMC) scaffolds loaded with different concentrations of rGO nanoparticles were synthesized via lyophilization. Characterization of these scaffolds showed that the rGO-loaded scaffolds retained the thermal and physical properties (swelling, porosity and in vitro biodegradation) of pure PVA/CMC scaffolds. In vitro cytotoxicity studies, using three different cell lines, confirmed that the scaffolds are biocompatible. The scaffolds containing 0.005 and 0.0075% rGO enhanced the proliferation of endothelial cells (EA.hy926) in vitro . In vivo studies using the chick chorioallantoic membrane model showed that the presence of rGO in the PVA/CMC scaffolds significantly enhanced angiogenesis and arteriogenesis.